Numerical and Experimental Evaluation of Stirred Tank with Tubular Baffles - Jesús E. Lugo Hinojosa; Juan A. Yañez Varela; Sergio Alejandro Martínez Delgadillo; Víctor X. Mendoza Escamilla; Clara G. Escarcega Ramirez (Chemical Engineering Transactions)
Agitated vessels are essential in many industrial processes to improve mass and heat transfer. These tanks consist of a vessel, a stirring system, and four baffles, which are critical to creating turbulent conditions by converting the tangential velocity component to an axial velocity component, thus creating homogeneous conditions throughout the tank. However, this also results in increased energy consumption. In this context, tubular baffles have emerged as a promising alternative, as previous studies have shown that they can reduce energy consumption. Various works have evaluated the effect of baffles on tank performance, but they often rely solely on experimental results or numerical simulations. This comprehensive study evaluates the effect of tubular baffles on flow patterns using Particle Image Velocimetry (PIV) and Computational Fluid Dynamics (CFD). The results showed a 12% reduction in energy consumption and an increase in flow through the impeller, resulting in a 20% increase in pumping efficiency when using tubular baffles. Tubular baffles were found to alter flow patterns, creating two main circulation loops: the first in the lower part of the tank, increasing flow circulation at the impeller, and the second in the upper part, with low flow reducing turbulent conditions. These findings highlight the potential of tubular baffles to optimize agitator tank operation and their relevance in industrial applications.